Design and transfer of OsSWEET14-editing T-DNA construct to bac thom 7 rice cultivar - Sam, Vu Hoai; Van, Pham Thi; Ha, Nguyen Thanh; Ha, Nguyen Thi Thu; Huong, Phung Thi Thu; Hoi, Pham Xuan; Phuong, Nguyen Duy; Quyen, Cao Le (Academia Journal of Biology, 2021)
Bac thom 7 rice (BT7 rice) is one of the major elite rice cultivars in Vietnam with superior productivity and quality but very susceptible to bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae. The gene OsSWEET14, belonging to the OsSWEET family which encodes sugar transport proteins, is considered to be a susceptible gene involved in the virulence of Xoo. At least three cis-elements (EBE - Effector-binding element), including Tal5, PthXo3 and AvrXa7 on BT7 OsSWEET14 promoter, bind specifically to well-known transcription activator–like effectors (TALEs) of many Asian Xoo bacterium strains. In this study, a T-DNA construct which expressed the protein-RNA complex CRISPR/Cas for editing three EBEs position on the OsSWEET14 promoter was designed. The recombinant binary vector was tested by PCR, restriction enzyme and finally sequencing and then successfully transferred to Bac thom 7 rice through Agrobacterium tumefaciens. 28 of 30 hygromycin-resistant regenerated rice lines that grew and developed normally under nethouse conditions were selected by PCR with specific primers. Among these, twelve transgenic rice lines were identified carrying one copy of the T-DNA construct. The presence of CRISPR/Cas9-induced mutations of the targeted promoter in the transgenic plants were confirmed by T7EI assay. These results provide the basis to determine the role of OsSWEET14 in the susceptibility of Bac thom 7 rice to Xanthomonas oryzae pv. oryzae -caused disease, towards the further goal of generating an improved Bac thom 7 rice variety with broad-spectrum bacterial leaf blight resistance using CRISPR/Cas9 technology.